ECCO Essential Requirements for Quality Cancer Care: Primary care. (October 2019) - Banks, Ian; Weller, David; Ungan, Mehmet; Selby, Peter; Aapro, Matti; Beishon, Marc; Bolt, Marije; Bonanno, Fiona; Champeix, Claire; Dégi, Csaba; Eneqvist, Lisa Jelf; Kazmierska, Joanna; et al.
Highlights: Primary care plays a major role in the diagnosis of cancer and care of patients Primary and community care are often not well integrated into cancer care There are many opportunities for extending care at the primary level Healthcare systems must consider new roles for primary and community professionals Abstract: Background: ECCO Essential Requirements for Quality Cancer Care (ERQCC) are checklists and explanations of organisation and actions that are necessary to give high-quality care to cancer patients. They are written by European experts representing all disciplines involved in cancer care. This paper concerns the integration of primary care into care for all cancers in Europe. Primary care integration: Primary care professionals play major roles in the diagnosis of cancer and care of cancer patients There are many opportunities for extending care at the primary level to cope with the increasing cancer burden and its nature as a chronic disease, but there are also significant barriers to progress towards high-quality patient-centred care To meet European aspirations for comprehensive cancer control, healthcare organisations must consider the requirements in this paper to include primary and community care in patient-centred pathways from diagnosis to treatment and survivorship.